Efficient hardware implementation of 2D convolutions, optimized for point cloud and adjustable to the 3D model requirements for object detection and classification - Pereira, Pedro Miguel Coelho (2021)
Dissertação de mestrado em Engenharia Eletrónica Industrial e Computadores (área de especialização em Sistemas Embebidos e Computadores)